Characterization of CD Marker Expression in Acute Myeloid Leukemia - Hikmat, Aisha; Salih, Shahlaa; Issa, Yasir (Journal of Madenat Alelem University College, 2023)
Acute Myeloid Leukemia (AML) is a heterogeneous hematological malignancy characterized by diverse subtypes and variable CD marker expressions. This study aimed to analyze the gender distribution, disease activity subtypes, and prevalence of CD markers in AML patients across different stages. A total of 160 participants were categorized into Control, Newly Diagnosed, Treated, and Relapsed groups. Blood samples were analyzed using flow cytometry for CD markers. Our findings revealed that the M2 subtype was the most prevalent among the Newly Diagnosed group. CD33 and CD13 were the most expressed markers across all stages. Notably, CD79A, CD10, and CD3 were absent in all AML subtypes. The study underscores the significance of CD markers in AML diagnosis, prognosis, and therapeutic targeting, emphasizing the disease’s complexity and the need for personalized treatment approaches.